(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3RHY (B: (3GdRhHYI hgj QjM JKjQ GdZHGQ hjQJaY Edi GdSeGA cCfg YehO , hJRHY GdQLd (B: (3Ci JZjX hGdRHY GdeYQHO s
(3BNQgG (B:s
(3ef aVd GdjGA HGH GddGe , bhdg (B: (3jdd bUQ GdCSfGf GdYdjG, hjbGd GfYcGagG Edi OGNd Gdae , hQLd Cjd , hGeQCI CjdGA Ci QejJge HSgGe , hjdjd ehVY ced HMeO Gddg gPG GdSaQ GdKGdK s
(3HChdgG MLI TQGA eDQNI SfI (B1126 (3g`s
(3fSNI KGdKI YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs